Evaluation of the Effects of Astragalus membranaceus on the Pharmacokinetics of Pemetrexed Disodium and Gemcitabine in Rats by a Simple High-Performance Liquid Chromatography/UV Method - Zixuan Chu; Zhiyuan Wang; Teng Liu; Shan Xiong; Bin Liu (Journal of Analytical Methods in Chemistry)
Combination therapy is opted as a potential therapeutic strategy for cancer treatment. Astragalus membranaceus combined with pemetrexed disodium or gemcitabine could reinforce the overall effects and alleviate the adverse effects. To investigate the effects of Astragalus membranaceus on the pharmacokinetics of pemetrexed disodium and gemcitabine, a HPLC method for simultaneous determination of pemetrexed disodium and gemcitabine in rat plasma was developed and validated. Chromatographic separation was achieved on a C18 column using a gradient mode containing water (containing 20 mM NaH2PO4 and 0.1% FA) and methanol at a flow rate of 0.8 mL/min. The specificity, linearity, recovery, stability, precision, and accuracy of the HPLC method were all validated. The rats were pretreated with Astragalus extract at the dosage of 3 g/kg for 20 consecutive days until we commence studying the pharmacokinetics of pemetrexed disodium or gemcitabine. There were no significant differences in pharmacokinetic parameters of pemetrexed disodium between the Astragalus extract treatment group and the control group. However, AUC, MRT, and Cl of gemcitabine were changed dramatically after treating with Astragalus extract (p<0.05). The AUC(0−t), AUC(0−∞), and MRT of gemcitabine decreased from 15747.12 ± 497.11 to 12312.41 ± 594.21 mg/L·min, 15976.18 ± 511.33 to 12489.59 ± 682.01 mg/L·min, and 97.83 ± 5.82 to 84.37 ± 2.79 min, respectively. The Cl of gemcitabine increased from 0.019 ± 0.0067 to 0.024 ± 0.0013 L/min/kg. The results showed that the pretreatment of Astragalus extract could exert an influence on the pharmacokinetic characteristics of gemcitabine in rats.